Hirsch's h-index: comparative analysis between Scopus, Web of Science and Google Scholar databases - Silva, Deise Deolindo [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2017)
Among the indicators to evaluate the scientific impact of publications, there is the Hirsch's h-index that, simultaneously, measures aspects related to the production and the impact of the scientific production of a researcher, periodical, group, research center or country on a database. In this context, this research aims to get the indices h to 20 researchers considered representative in the theme Metric Studies of Information, on three distinct data sources (Scopus, Web of Science and Google Scholar), in order to identify and to analyze possible differences between the values of these indicators, examining the consistency of the indices in these information sources. To this end, the h-index for each investigator in the mentioned platforms was surveyed. By means of the Wilcoxon-Mann-Whitney test, using a 5% significance level, it was identified that the h-indices did not differ statistically between the Scopus and Web of Science databases. On the other hand, this index differed significantly in relation to the values obtained from Google Scholar.
Keywords: Information metric studies; H-index; Domain analysis; Databases